2016
DOI: 10.1371/journal.pone.0152755
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Containing Anti-Biofilm Nanofiber Scaffolds as a Wound Dressing Material

Abstract: Copper particles were incorporated into nanofibers during the electrospinning of poly-D,L-lactide (PDLLA) and poly(ethylene oxide) (PEO). The ability of the nanofibers to prevent Pseudomonas aeruginosa PA01 and Staphylococcus aureus (strain Xen 30) to form biofilms was tested. Nanofibers containing copper particles (Cu-F) were thinner (326 ± 149 nm in diameter), compared to nanofibers without copper (CF; 445 ± 93 nm in diameter). The crystalline structure of the copper particles in Cu-F was confirmed by X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…Some authors (Heliopoulos et al, 2013) used wool fabric with an alginate and copper ions coating as an antimicrobial agent using the example of E. coli. Ahire et al (2016) investigated in their study the influence of copper nanoparticles that were incorporated into nanofibers during the electrospinning of poly-D,llactide(PDLLA) and poly(ethyleneoxide) on biofilm formation. As a result, it was found that the biofilm formation of P. aeruginosa and S. aureus decreased by 41% and 50%, respectively, due to copper released from the nanofibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors (Heliopoulos et al, 2013) used wool fabric with an alginate and copper ions coating as an antimicrobial agent using the example of E. coli. Ahire et al (2016) investigated in their study the influence of copper nanoparticles that were incorporated into nanofibers during the electrospinning of poly-D,llactide(PDLLA) and poly(ethyleneoxide) on biofilm formation. As a result, it was found that the biofilm formation of P. aeruginosa and S. aureus decreased by 41% and 50%, respectively, due to copper released from the nanofibers.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that nanoparticles reveal new features due to quantum-size effects and, consequently, reactivity and biological activity growth (Khezerlou et al, 2018). In previous works (Borkow et al, 2009;Ahire et al, 2016;Khan & Yaqoob, 2017) the positive effect of nanoparticles of such metals as Cu in connection with bactericidal properties was considered. Disinfectant properties of Cu alloys surfaces were determined but Cu antibacterial activity mechanisms, its antimicrobial properties and ability to impact microbial biofilm formation (Agarwala et al, 2014;Jamal et al, 2018) are still not systematically understood and are only covered in scattered studies.…”
Section: Introductionmentioning
confidence: 99%
“…Ahire et al incorporated copper nanoparticles into nanofibers through the electrospinning of PEO and Poly-D, L-lactide. After 48 h at the presence of Cu-nanofibers, S. aureus and P. aeruginosa were reduced by 50% and 41%, respectively 89 .…”
Section: Electrospunmentioning
confidence: 98%
“…Copper particles After 48 h biofilm formation by S. aureus Xen 30 and P. aeruginosa PA01S. was reduced by 50% and 41%, respectively [273] Tissue engineering Poly (l-lactide-co-glycolide)/ (PLGA/PLLA)…”
Section: Vancomycin (Van) Linezolid (Lin) and Daptomycin (Dap)mentioning
confidence: 99%